(untitled) (AYUSHDHARA, 2019)
Chronic musculoskeletal disorders are topic of concern for all available systems of treatment. Incidence of musculoskeletal disorders is increasing due to life style changes. Advancement in the field of trauma and acute cases management is commendable in the contemporary science but in case of chronic musculoskeletal disorders there are limited options such as NSAIDS, steroids etc. So there is always a thirst for more options. Marma therapy is capable of curing the chronic musculoskeletal diseases when practiced by skilled expert. Marma therapy is non-invasive modality of treatment in which calculated amount of pressure is applied to vital points called Marma in order to relieve pain. Acharya Sushruta has given detailed description of Marma in Pratyek Marmanirdeshsharir chapter of Sharir Sthana of Sushruta Samhita. Present study is an effort to provide the basic information with indications and methods of application of Marma therapy as this technique is non-invasive still effective in providing temporary as well as permanent relief in signs and symptoms of chronic musculo-skeletal disorders. Detailed review of literature including Brihattrayi along with available articles on the topic under consideration was done for critical analysis of proposed concepts.